2010
DOI: 10.1183/09031936.00100510
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency is common in idiopathic pulmonary arterial hypertension

Abstract: The aims of this study were to assess the prevalence of iron deficiency in idiopathic pulmonary arterial hypertension (IPAH) and investigate whether oral iron supplementation has effects in iron-deficient patients.Iron parameters were measure for all IPAH patients attending our centre (VU University Medical Center, Amsterdam, the Netherlands) between May 2009 and February 2010. Iron data were related to clinical parameters, including 6-min walking distance (6MWD), and haemodynamic parameters measured during ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
200
1
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(225 citation statements)
references
References 27 publications
(39 reference statements)
13
200
1
11
Order By: Relevance
“…In addition, in contrast to oral iron treatment, which does not produce a response in 44% of ID iPAH patients, ferric carboxymaltose led to higher iron stores in all patients, as represented by increased ferritin levels. 2 Figure 2. Oxygen handling in quadriceps muscle fibers after iron therapy in iron-deficient idiopathic pulmonary arterial hypertension patients.…”
Section: Intravenous Iron Safely Increased Body Iron Stores and Qualimentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in contrast to oral iron treatment, which does not produce a response in 44% of ID iPAH patients, ferric carboxymaltose led to higher iron stores in all patients, as represented by increased ferritin levels. 2 Figure 2. Oxygen handling in quadriceps muscle fibers after iron therapy in iron-deficient idiopathic pulmonary arterial hypertension patients.…”
Section: Intravenous Iron Safely Increased Body Iron Stores and Qualimentioning
confidence: 99%
“…5 We have shown that oral iron supplements are ineffective in restoring body iron stores in iPAH. 1,2 Recently, it was demonstrated that intravenous iron treatment in ID iPAH patients was associated with higher serum iron levels, improved 6-minute walk distance (6MWD), and quality of life. 6,7 However, the exact mechanisms by which iron improves clinical performance in iPAH patients remain to be elucidated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 These observations pointed to the possibility that iron status may influence the expression of pulmonary hypertension in Chuvash polycythemia as well. Furthermore, iron deficiency is common in patients with idiopathic pulmonary hypertension [15][16][17] and pulmonary hypertension secondary to cyanotic congenital heart disease, 18 and is associated with reduced exercise capacity. [16][17] Iron therapy improved exercise capacity in such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, iron deficiency is common in patients with idiopathic pulmonary hypertension [15][16][17] and pulmonary hypertension secondary to cyanotic congenital heart disease, 18 and is associated with reduced exercise capacity. [16][17] Iron therapy improved exercise capacity in such patients. 18 Congenital polycythemia is a rare disorder that occurs sporadically around the world.…”
Section: Introductionmentioning
confidence: 99%